Savage sight/constructed noise : poetic adaptations of painterly techniques in the French and American avant-gardes - Sweet, David LeHardy, 1961- (North Carolina studies in the Romance languages and literatures ;, 2003)
"This book examines poetic adaptations of painterly techniques in works by writers such as Guillaume Apollinaire, Pierre Reverdy, Andre Breton, Frank O'Hara, and John Ashbery - all chosen for the experimentalism of their poetry as well as for the quality of their critical writings on art. Close attention is paid to essays on painters identified with Cubism, Futurism, and Dada-Surrealism in France and with Abstract Expressionism and New Realism in the United States."